Physiological determinants of repeated sprint ability in male team sport players - Hoker, J.; Ellis, L. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
The physiological determinants of repeated sprint ability (RSA) are an area of current debate (Bishop & Edge, 2006; Racinais et al., 2007; Billaut & Smith, 2010). The fatigue mechanisms that contribute to performance decrements in repetitive short-duration sprints remain elusive. To the author`s knowledge no studies have simultaneously tracked changes in heart dynamics, pulmonary gas exchange, muscle oxygenation kinetics and muscle activation to determine whether central or peripheral mechanisms lead to performance impairment. Nine male team sport players (mean + standard deviation: Age 21±2 yr; VO2max 48.9±6.9 ml•kg-1•min-1) completed a test to maximal volitional exhaustion (Hopker et al., 2012), and on a separate day, a repeated sprint test on a cycle ergometer consisting of 10 x 6s maximal sprints interspersed by 30s of passive recovery. Prior to both maximal and RSE tests, participants undertook a 5 minute period of rest to facilitate baseline measurements and a 10 minute warm-up at 100W. Throughout the test, oxygen uptake was measured on a breath-by-breath basis, and tissue oxygen saturation index (TSI%) and total hemoglobin concentration (tHb) of the left vastus lateralis (VL) muscle was assessed using spatially resolved spectroscopy NIRS. Surface RMS EMG of the left VL muscle and power output were recorded for each sprint repetition. Cardiac output was assessed continuously throughout the test using the non-invasive thoracic electrical bioimpedance method (Charlouw et al., 2000). Data for each variable were analysed using a one-way ANOVA with repeated measures. A post hoc least significant difference test was used when necessary to determine where significant differences occurred. Values are mean ± standard deviation. Power output demonstrated a significant decline during the test (-209±83W, p<0.05). There was also a significant progressive decline in muscle TSI% (-15.0±7.5%, p<0.05) over the repeated sprints (see Figure 1). Regional muscle blood volume (as shown by changes in tHb) significantly declined at the first sprint (see Figure 1) compared to baseline (-8.1±6.8 ìM•cm, p<0.05), and then remained consistent across the rest of the test. Muscle reoxygenation rate during recovery periods remained constant throughout the test (p>0.05), showing that availability of O2 to the muscle was well preserved. The activation of the VL muscle (taking the 2nd and 3rd pedal revolution) changed significantly across the sprint repetitions (sprint 1: 0.36±0.12 mV vs. sprint 10: 0.30±0.09 mV, p<0.05). VO2 and cardiac output significantly increased across the RSE test (+11.4±5.9 ml/kg/min and +6.9±5.0 L/min respectively, p<0.05), but were both significantly lower (p<0.05) than the values recorded during the maximal test. In conclusion, the results of this study suggest that short-duration RSA is determined by both muscle desaturation and changes in muscle activation.